Determination of features of development of modern theories of management - Zhaldak, Hanna (Technology audit and production reserves, 2021)
The object of research is the processes of development of modern management theories. One of the next problematic aspects is the identification of the peculiarities of the development of modern management theory in the period of digitalization and pandemic, which means a significant impact on the economy. In the process of work general scientific methods were used: induction and deduction, analysis and synthesis, comparison, systematization. The analysis of scientific approaches to the definition of management is carried out; the main essential features of modern enterprises and management theories, respectively, are determined. It is determined that the theory of management at the present level undergoes significant transformations. In modern theories more and more attention is paid to: the intangible component and the peculiarities of its management; there is an active transition to digital technologies and digitalization of business; there is a need to use new management methods; organizational structures and corporate cultures are changing. This in turn contributes to the purposeful formation and development of such institutions within the organization as: – trust and creative atmosphere of productive group work; – development of organizational ties within the organization and outside it; – development of innovative ability of the company’s staff; – use of experience of other organizations. Based on the analysis, the following features of modern management theories are identified: – in modern theories more and more attention is paid to the intangible component and the peculiarities of its management; – active transition to digital technologies and digitalization of business; – change in the subject of work in most employees, in particular, the transition to advanced information and communication technologies; – the need to use new management methods; – transformation of organizational structures and corporate cultures. This provides the possibility of effective modern management by planning the activities of the firm in the short, medium and long term, as well as obtaining the maximum possible profit with minimal costs in a rapidly changing environment.